Analysis of the Catecholaminergic Phenotype in Human SH-SY5Y and BE(2)-M17 Neuroblastoma Cell Lines upon Differentiation - Filograna, Roberta; Civiero, Laura; Ferrari, Vanni; Codolo, Gaia; Greggio, Elisa; Bubacco, Luigi; Beltramini, Mariano; Bisaglia, Marco (PloS one, 2015)
Human cell lines are often used to investigate cellular pathways relevant for physiological or pathological processes or to evaluate cell toxicity or protection induced by different compounds, including potential drugs. In this study, we analyzed and compared the differentiating activities of three agents (retinoic acid, staurosporine and 12-O-tetradecanoylphorbol-13-acetate) on the human neuroblastoma SH-SY5Y and BE(2)-M17 cell lines; the first cell line is largely used in the field of neuroscience, while the second is still poorly characterized. After evaluating their effects in terms of cell proliferation and morphology, we investigated their catecholaminergic properties by assessing the expression profiles of the major genes involved in catecholamine synthesis and storage and the cellular concentrations of the neurotransmitters dopamine and noradrenaline. Our results demonstrate that the two cell lines possess similar abilities to differentiate and acquire a neuron-like morphology. The most evident effects in SH-SY5Y cells were observed in the presence of staurosporine, while in BE(2)-M17 cells, retinoic acid induced the strongest effects. Undifferentiated SH-SY5Y and BE(2)-M17 cells are characterized by the production of both NA and DA, but their levels are considerably higher in BE(2)-M17 cells. Moreover, the NAergic phenotype appears to be more pronounced in SH-SY5Y cells, while BE(2)-M17 cells have a more prominent DAergic phenotype. Finally, the catecholamine concentration strongly increases upon differentiation induced by staurosporine in both cell lines. In conclusion, in this work the catecholaminergic phenotype of the human BE(2)-M17 cell line upon differentiation was characterized for the first time. Our data suggest that SH-SY5Y and BE(2)-M17 represent two alternative cell models for the neuroscience field.